2017
DOI: 10.1111/edt.12341
|View full text |Cite
|
Sign up to set email alerts
|

The risk of healing complications in primary teeth with intrusive luxation: A retrospective cohort study

Abstract: Over 80% of the intruded primary teeth re-erupted spontaneously. However, nearly one-third of the teeth showed complications such as pulp infection/periapical inflammation or ankylosis, which could potentially affect the development of the permanent incisor. Therefore, patients should be monitored regularly, especially during the first year after injury, to diagnose and treat complications in time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(90 citation statements)
references
References 23 publications
3
81
0
6
Order By: Relevance
“…The FEA results showed the highest impact stresses in the surrounding bone and soft tissue for the model of a 3.5‐year‐old child with no physiological root resorption of the primary tooth. The stress concentrations in the surrounding bone and soft tissue seem to correlate with areas instigated in complications of the root and crown formation phase . The analysis also indicated that impact to a primary incisor with complete root (children aged 3.5 years old) caused less stress and strain on the permanent tooth germ compared to teeth with more root resorption (5‐6 years old).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The FEA results showed the highest impact stresses in the surrounding bone and soft tissue for the model of a 3.5‐year‐old child with no physiological root resorption of the primary tooth. The stress concentrations in the surrounding bone and soft tissue seem to correlate with areas instigated in complications of the root and crown formation phase . The analysis also indicated that impact to a primary incisor with complete root (children aged 3.5 years old) caused less stress and strain on the permanent tooth germ compared to teeth with more root resorption (5‐6 years old).…”
Section: Discussionmentioning
confidence: 91%
“…The sequelae in these cases might affect root development of the permanent tooth germ as root dilacerations, which are less common compared to complications for a permanent crown . Trauma to the primary incisor through pulp necrosis and infection with periapical abscesses has been reported to have the potential to damage the development of a permanent tooth . In the current impact model of a primary incisor without full root resorption (model of 3.5 years old), the apex of the primary incisor was compressed against the bone barrier, causing high stresses at its apex.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The risk of the potential consequences in the permanent dentition is well documented . However, due to the variations in the study designs and presentation of results, it is difficult to make comparisons between the published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is apparent that the more severely affected the primary tooth is, the higher the frequency of developmental disturbance in the permanent succesor . Concussion and subluxation injuries are reported to cause minimal consequences (8.3%) to their permanent successors . Tooth discoloration and subsequent pulp necrosis and infection of the affected primary teeth are the most commonly reported sequelae following subluxation injuries .…”
Section: Discussionmentioning
confidence: 99%